2020
DOI: 10.1590/fst.17319
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterization, antioxidant activity, and sensory analysis of beers brewed with cashew peduncle (Anacardium occidentale) and orange peel (Citrus sinensis)

Abstract: This study aimed at brewing wheat beer with cashew peduncle (CP) and orange peel (DP). Six formulations (F) were assessed for their physicochemical characteristics and total amount of polyphenols and antioxidant activity. The flavors of F1 and F6 were evaluated via sensory analysis. The results showed that the evaluated beers were in accordance with the parameters required by the Brazilian legislation. Moreover, the addition of CP and DP improved total amounts of polyphenols, antioxidant activity, and flavor. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 31 publications
0
17
1
1
Order By: Relevance
“…Interestingly, the citrus × clementina juice enriched with this extract (20% v/w) increased its antioxidant potential. Similarly, Pereira et al (2020) reported the increase of beer antioxidant activity after addition of orange peels extract. (Ramli et al, 2020).…”
Section: Antioxidant Effectsmentioning
confidence: 86%
“…Interestingly, the citrus × clementina juice enriched with this extract (20% v/w) increased its antioxidant potential. Similarly, Pereira et al (2020) reported the increase of beer antioxidant activity after addition of orange peels extract. (Ramli et al, 2020).…”
Section: Antioxidant Effectsmentioning
confidence: 86%
“…The regionality of the adjuncts is only poorly evaluated; however, intriguingly, attention is placed on the use of by-products from the food industry [96,132], with the incremental aim of reducing food waste and its economic weight.…”
Section: Olive Leaves Italymentioning
confidence: 99%
“…Based on the latest research, beers' physicochemical analysis has been mainly based on the bioactive compounds in craft beers [1], volatiles, and antioxidant properties when adding fruit using gas chromatography/mass-spectroscopy (GC-MS) and high-performance liquid chromatography (HPLC) [1][2][3]. Many other studies coupled these analyses of quality traits with sensory trials when analyzing processes to change beer characteristics, such as ultrasound-assisted thermal processing [4], antioxidant activity through natural additives [5][6][7], for sweet potato beers [8] and commercial beers [9]. In the case of traditional consumer sensory tests, they tend to be subjective, and require a laboratory with individual booths that meet specific requirements; it also involves the recruitment of a large number of participants, which often requires an incentive to participate, which leads to higher costs and time for conducting the sessions and analyzing the data [10][11][12].…”
Section: Introductionmentioning
confidence: 99%